2017
DOI: 10.1088/1742-6596/908/1/012003
|View full text |Cite
|
Sign up to set email alerts
|

The weathering effect in natural environment on kenaf blast and unsaturated polyester composite

Abstract: The weathering effect in natural environment on kenaf blast and unsaturated polyester composite Abstract.A Kenaf composite was prepared by using hand lay-up process. The effect of weather on mechanical, morphology and thermal properties of kenaf composite were studied. Tensile strength of kenaf compositewas found to be 60MPa. Unfortunately, tensile strength of thecomposite starts to decrease after the first weathering month through to the weathering periods with constant reduction of tensile, at the end of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Numerous drawbacks of NFr include decreased strength, decreased interfacial adhesion, poor moisture absorption resistance, and reduced durability and dimensional stability. To overcome these constraints, different methods for NFr modification have been proposed [26]. Four different approaches are used for treating NFr, physical processes, chemical methods, biological methods, and nano enhance photocatalysis treatment.…”
Section: Impact Of Surface Treatment Of Natural Fiber On Moisture Abs...mentioning
confidence: 99%
“…Numerous drawbacks of NFr include decreased strength, decreased interfacial adhesion, poor moisture absorption resistance, and reduced durability and dimensional stability. To overcome these constraints, different methods for NFr modification have been proposed [26]. Four different approaches are used for treating NFr, physical processes, chemical methods, biological methods, and nano enhance photocatalysis treatment.…”
Section: Impact Of Surface Treatment Of Natural Fiber On Moisture Abs...mentioning
confidence: 99%
“…140 The weathering effect on the degree of degradation of biobres can be reduced by the incorporation of synthetic bres to form a hybrid biocomposite. Mohammed et al 143 reported superior thermal stability of kenaf bre/GF polyester as compared to only kenaf bre/polyester biocomposites when exposed to natural weathering for 3 months. The T g of the composites were found to decrease with an increasing weathering period due to the molecular weight reduction in the polyester.…”
Section: Retention Rate ¼mentioning
confidence: 99%